FACTORS SLOW SECONDARY LEARNESR DIFFICULTIES IN LEARNING SPEAKING AT HOMESCHOOLING - Devi . Lusiana; Anni Holila Pulungan; Rahmad . Husein (Universitas Negeri Medan, 2021)
ABSTRACTThis research deals with factors slow secondary learners difficulties in learning speaking at Homeschooling Global Lentera Kasih Batam. This research was conducted by using qualitative research. The objectives of this study was to investigate the factors causing slow secondary learners difficulties in learning speaking English. The data of this study obtained from documentation and interview. The techniques of collecting data that was applied in this research- they are observation, interview and documentation. The data of this study obtained from the result of interview from teacher and parents of slow learners. The source of data in this study was slow secondary learners grade X and the English teacher. There were 2 English teachers, and 2 classes of secondary level learners in Homeschooling Global Lentera Kasih and both slow learners classes contains 4 students, in class X-1 they are FL, NM, RRH and PLG, while in class X-2, they are DA, KT, SRN and FDF. The results showed that there were two factors caused the difficulties of slow learners in learning speaking, they are emotional and personal factors. Keywords: Factors, Slow Learners, Difficuties , Learning, Homeschooling